INFORMATION SYSTEM AND VILLAGE MANAGEMENT TO IMPROVE THE REGIONAL ECONOMY AND COMMUNITY PRODUCTIVITY - Imran, Muhammad Alief Fahdal; Zainuddin, Zahir; Imran, Haliah; Hasan, Hasnawiya; Oemar, Imran (Faculty of Engineering UNHAS, 2023)
Indonesia is an archipelago with most of its territory in rural areas that have a lot of potential to develop, including its natural potential, cultural potential, and community potential. These potentials can be developed to improve the regional economy and ideal productivity. Of course, infrastructure such as IT and communication facilities and human resources must support this. Ekatiro Village, located in Bontotiro District, Bulukumba Regency, South Sulawesi Province, is one of the villages that has natural and cultural tourism potential that can be improved by utilizing technology. The method used to obtain information on the tourism and cultural potential of Ekatiro Village is a case study and data analysis. Starting from document searches, surveys and interviews of UMKM actors, and documentation of tourist destinations. This document search was carried out together with Ekatiro Village officials and the search for potential tourist destinations was carried out by direct search in the Ekatiro Village area. The results of the discussion showed that there is a lot of potential to improve the regional economy with the use of this village information and management system. Furthermore, the website of Ekatiro Village was created using PHP, Javascript, Laravel, and CSS programming languages. Keywords: Information Systems; Local UMKM; Regional Economy; Tourist Destinations; Utilization of Technology. As well as socialization and training on the use of website information systems so that participants get a lot of convenience in terms of accessing the Ekatiro Village information system. One of the objectives of creating an information and management system for Ekatiro Village is to improve the welfare of the village community, empower partner village communities to be more productive, and apply digital information technology to services and general information on tourism and local UMKM.